2022
DOI: 10.3390/cancers14051145
|View full text |Cite
|
Sign up to set email alerts
|

Immune Checkpoint Inhibitors—Associated Cardiotoxicity

Abstract: Large population-based studies examining differences in ICI-associated cardiotoxicity across cancer types and agents are limited. Data of 5518 cancer patients who received at least one cycle of ICIs were extracted from a large network of health care organizations. ICI treatment groups were classified by the first ICI agent(s) (ipilimumab, nivolumab, pembrolizumab, cemiplimab, avelumab, atezolizumab, or durvalumab) or its class (PD-1 inhibitors, PD-L1 inhibitors, CTLA4-inhibitors, or their combination (ipilimum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 49 publications
0
17
1
Order By: Relevance
“…A large population-based study from multiple medical institutions showed that patients with CAEs had a higher burden of comorbidities than patients who did not develop CAEs within 1 year of ICIs initiation ( P = 0.0042). Patients who developed CAEs were more likely to have cerebrovascular disease (12.9% vs. 10.3%, P = 0.0375), congestive heart failure (5.9% vs. 2.6%, P < 0.001), myocardial infarction (4.8% vs. 2.3%, P = 0.0002), peripheral vascular disease (15.6% vs. 12.3%, P = 0.0129), hypertension (50.8% vs. 45.1%, P = 0.0046), or renal disease (13.7% vs. 10.8%, P = 0.0221) ( 7 ). In addition, an international registry identified combination therapy, diabetes, obesity, and anti-CTLA-4 therapy were independent risk factors for cardiotoxicity ( 10 ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A large population-based study from multiple medical institutions showed that patients with CAEs had a higher burden of comorbidities than patients who did not develop CAEs within 1 year of ICIs initiation ( P = 0.0042). Patients who developed CAEs were more likely to have cerebrovascular disease (12.9% vs. 10.3%, P = 0.0375), congestive heart failure (5.9% vs. 2.6%, P < 0.001), myocardial infarction (4.8% vs. 2.3%, P = 0.0002), peripheral vascular disease (15.6% vs. 12.3%, P = 0.0129), hypertension (50.8% vs. 45.1%, P = 0.0046), or renal disease (13.7% vs. 10.8%, P = 0.0221) ( 7 ). In addition, an international registry identified combination therapy, diabetes, obesity, and anti-CTLA-4 therapy were independent risk factors for cardiotoxicity ( 10 ).…”
Section: Discussionmentioning
confidence: 98%
“…Data from a large network of healthcare organizations showed that of 5,518 cancer patients treated with at least one ICI cycle, 691 (12.5%) developed cardiotoxicity. The most common cardiotoxicity was arrhythmia (9.3%), and 2.1% of the patients developed myocarditis at 12 months ( 7 ). In this real-world study, we found that the incidence rate of CAE in patients who received at least four cycles of ICI within 1 year was 12.93%.…”
Section: Discussionmentioning
confidence: 99%
“…ICI-associated cardiotoxicity is a rare occurrence that may be fatal. Although data from a large population-based epidemiology study indicated no difference between PD-1 and PD-L1 inhibitors in terms of risk of cardiotoxicity, patients initiated on pembrolizumab were vulnerable to developing cardiotoxicity ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…The ICI related myocarditis is generally considered highly arrhythmogenic and fatal; however, the exact pathogenesis is still poorly recognized and understood ( 12 , 13 ). Myocarditis caused by ICIs represents <1% of immune-related adverse events.…”
Section: Discussionmentioning
confidence: 99%